2015
DOI: 10.1017/s136898001500302x
|View full text |Cite
|
Sign up to set email alerts
|

Underweight and mortality

Abstract: Objective: According to most prospective studies, being underweight (BMI <18·5 kg/m 2 ) is associated with significantly higher mortality than being of normal weight, especially among smokers. We aimed to explore in a generally lean population whether being underweight is significantly associated with increased all-cause mortality. Design: Prospective cohort study. Setting: Korea Medical Insurance Corporation study with 14 years of follow-up. Subjects: After excluding deaths within the first 5 years of follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…Jee et al reported that underweight men and women had higher mortality; 10 however, a recent Korean study found that underweight was not associated with increased mortality compared to a normal-weight population. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Jee et al reported that underweight men and women had higher mortality; 10 however, a recent Korean study found that underweight was not associated with increased mortality compared to a normal-weight population. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Low body mass index (BMI) is a well-known risk factor of osteoporosis8 and diabetes 9. Studies have shown that mortality is increased with being underweight 10,11…”
Section: Introductionmentioning
confidence: 99%
“…cohort consisted of 115,200 men and 67,932 women aged 35-59 years who underwent health examinations in 1990 (95% participation rate) and 1992 (94% participation rate). The study was composed of a 25% random sample of male workers and all female workers [15]. Data on fasting serum glucose levels and major cardiovascular risk factors for 108,461 men and 64,119 women were available.…”
mentioning
confidence: 99%